À propos des illégalismes privilégiés. Réflexions conceptuelles et mise en contexte - Acosta, Fernando (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1988)
The resolution of conflicts in a society can be seen as a complex network of interactions between various relatively autonomous official control systems. The place occupied by the criminal law as well as its role within this network are larg e -ly determined by the nature of its relations with the other control systems. Based on these theoretical premises, developed in recent socio-juridical studies, this article advances a number of conceptual proposals aimed at clarifying a question that has been the subject of theoretical and political controversy in the field of criminology for about half a century. It is the question of the exclusion, total or partial, of certain particular forms of illegalities from penal intervention. The principal characteristic of these illegalities lies in the fact that they have a broad range of forms of control (civil, administrative proceedings and particularly amicable arrangements). The control of illicit activities in five areas of social life examined in the second part of the study (the business world, public administration, public health, the environment and health and safety in the workplace) show this characteristic very clearly. In conclusion, the author advances a number of arguments that tend to illustrate the profoundly illusory nature of any attempt at control of the above-mentioned illicit activities by intervention of the criminal law.